RANCANG BANGUN SISTEM ANALISIS NILAI SISWA SDN 13 PAGI DUREN SAWIT BERBASIS ETL DAN OLAP - Agus Wismo Widodo; Dian Gustina; Muhammad Ichsan Fikri (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
Rapid information technology growth prompts the integration of information systems for managingstudent grades as a basis for learning evaluation. Currently, SDN 13 Pagi Duren Sawit manages thesegrades manually, separating the odd and even semesters, which hinders teachers from performingsystematic analysis and comparisons. This study designs an analytical system using Extract, Transform,Load (ETL) and Online Analytical Processing (OLAP) to integrate and structure student grademanagement. Utilizing an applied research method with the Waterfall SDLC approach, the ETL processensures data consistency, while OLAP enables multidimensional analysis by student, subject, andsemester. The web-based system was verified through Black Box Testing and evaluated using the SystemUsability Scale (SUS)